Mortuary: The Inevitable Evil: Mortuary Staff is a Victim of the Sudden Death Caused by the Invisible Mycoburden of Human Cadavers - Al-Jobory, Hala J; Al-Amoodi, Shaima’a A; Al-Shamerie, Salwa A; Al-Samawi, Kholod K (PSM Microbiology, 2018)
Working in a mortuary is an extremely stressful and lethal experience, as repeated exposure to different fungal spores, makes the staff as victims of sudden death. The presence of invisible mycoburden on human cadavers and rule out their effect on mortuary staff health was the aim of this research. A total of 20 cadavers along with 79 samples from different surfaces were collected in the city of Sana’a, Yemen, from governmental and private owned hospitals. After submitting to conventional mycological procedures, Aspergillus spp., Penicillium spp. and Candida spp. were the main fungal isolates in both bloated and putrefied stage, while each of Eurotium spp. and Mucor spp. predominated the skeletonized stage. Massive fungal load was detected on different mortuary surfaces, except for draining boards and necropsy tables. Among the identified species in both of cadavers and surfaces; Cladosporium cladosporioides, Histoplasma sp. and P. marneffei are classified in risk group 3, A. flavus, A. fumigatus and Candida albicans in risk group 2, which pose an allergic potential risk, while others are listed in the risk group 1, even if they may not found significant, it obviously represent serious risk for personnel working there especially those with open scare causing uncommon human disease. Safe working conditions for handling cadavers are recommended along with proper education, use of protective clothing and practice of hygiene measures.